(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The development of nanoparticle reinforced composites is presently one of the most explored areas in materials science and engineering. Multiscale composites can be produced with superior properties by combining nanoparticles with traditional reinforcement materials. This research focuses on the development of such composites, through the use of carbon nanofibers (CNFs), carbon fibers and modified epoxy resin for structural and impact applications. Flexural and tensile behavior of composites has been analysed to investigate the effect of modification of epoxy matrix by adding CNFs on the mechanical properties of composites. Better strengths are obtained at 2.5 wt% of Epoxy terminated butadiene-acrylonitrile copolymer (ETBN) and 2 wt% of Carbon nanofibers (CNF) in the polymer hybrid nanocomposite. Morphological and fracture analysis of composites were performed by SEM DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11451 Bangladesh J. Sci. Ind. Res. 47(2), 191-196, 2012